2018
DOI: 10.1055/s-0038-1669786
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Involvement in Glycogen Storage Disease Type III in Fifty Tunisian Patients: Phenotype and Natural History in Young Patients

Abstract: Background Our aim was to describe the natural history of neuromuscular involvement (NMI) in glycogen storage disease type III (GSDIII). Methods We conducted a longitudinal study of 50 Tunisian patients, 9.87 years old in average. Results NMI was diagnosed at an average age of 2.66 years and was clinically overt in 85% of patients. Patients with clinical features were older (p = 0.001). Complaints were dominated by exercise intolerance (80%), noticed at 5.33 years in average. Physical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This causes glycogen accumulation in the liver, skeletal muscle, and myocardium, resulting in liver enlargement, fasting hypoglycemia, delayed normal growth, and progressive muscle weakness (1). GSD IIIa is mostly diagnosed in infants and during early childhood; late-onset GSD IIIa in middle age is relatively rare (2). This study reported a patient aged 40 years who was diagnosed as GSD IIIa by muscle biopsy.…”
Section: Introductionmentioning
confidence: 91%
“…This causes glycogen accumulation in the liver, skeletal muscle, and myocardium, resulting in liver enlargement, fasting hypoglycemia, delayed normal growth, and progressive muscle weakness (1). GSD IIIa is mostly diagnosed in infants and during early childhood; late-onset GSD IIIa in middle age is relatively rare (2). This study reported a patient aged 40 years who was diagnosed as GSD IIIa by muscle biopsy.…”
Section: Introductionmentioning
confidence: 91%
“…The median age of onset of CK elevation was reported to be 10 years[ 170 ]. Although muscle involvement becomes clinically more obvious later in life, mild muscle weakness on physical examination, motor developmental delay (delayed sitting, delayed standing upright, delayed onset of walking), exercise intolerance, and hypotonia were reported in the majority of pediatric patients with GSD-III[ 174 - 176 ]. Muscle weakness and wasting may slowly progress and become severe by the third or fourth decade of life[ 165 , 173 ].…”
Section: Gsds Involving Livermentioning
confidence: 99%
“…Myopathy can be proximal, distal, or more generalized. Exercise intolerance with muscle fatigue, cramps and pain are evident in more than half of patients[ 170 , 174 , 175 ]. Bulbar or respiratory dysfunctions are rarely seen in GSD-III patients while no clinical involvement of facial or ocular muscles has been described in the literature[ 178 ].…”
Section: Gsds Involving Livermentioning
confidence: 99%
“…The possible coexistence of peripheral nerves involvement remains debated, and is suggested in adult patients presenting distal muscular weakness [ 38 41 ]. This distal muscular weakness is probably the consequence of distal myopathy, and a recent study of a series of 16 patients, who all underwent an ENMG following the standard protocol, did not show any sign of peripheral nerve damage [ 42 ].…”
Section: Diagnosis and Initial Assessmentmentioning
confidence: 99%